Research on the Relation between Agro-forestry Livelihood and Carbon Storage in Vo Mieu Commune, Thanh Son District, Phu Tho Province - Thanh, Nguyen Thi Ha; Tai, Vu Anh; An, Bui Hai (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Many researches over the world have been conducted to prove that agriculture-forestry activities positively affect on carbon storage, as agro-forestry system is one of two main factors (together with ocean) affecting sequestration of atmospheric carbon dioxide. However, researches on the relationship between livelihood activities and carbon storage have not yet been well concerned in Vietnam. Vo Mieu is a mountainous commune of Thanh Son district, Phu Tho province. People here live mostly depending on cropland including plantation. To conduct this research, we used two main methods including household survey (90 questionnaires), and statictics-analysis and evaluation. This research aims to layout the relationship between economic efficiency and carbon storage of main agroforestry activities in Vo Mieu by kinds of plants and geographical location. Different plants provide different carbon storage and also different economical effectiveness. Tea plantation provides not only the highest economical effectiveness but also the highest carbon storage. Carbon storage is accounted differently between villages. The livelihood change and land use at locality showed a trending of improving carbon storage and turnover, but that change has just been spotaneous. The result of this research can be used for planning suitable livelihood activities for people in Vo Mieu toward sustainable development. Keywords Livelihood activities, carbon storage, agro-forestry, Vo Mieu Commune References [1] IPCC (2000), Land use, Land-use change, and Forestry, Report, Cambridge University Press, Cambridge, UK, p375. [2] United Nations (1998), Kyoto Protocol to the United Nations Framework Convention on Climate Change. [3] ATTRA, Indu K.Murthy, Mohini Gupta, Sonam Tomar, Madhushree Munsi, Rakesh Tiwari, GT Hegde and Ravindranath NH (2013), Carbon Sequestration Potential of Agroforestry Systems in India, Earth Science & Climate Change, Volume 4, Issue 1, pp.1-7. [4] RECOFTC-Trung tâm vì con người và Môi trường (2013), Một số thuật ngữ liên quan tới biến đổi khí hậu và REDD+. [5] Joyotee Smith and Sara J. Scherr (2002), Forest Carbon and Local Livelihoods: Assessment of Opportunities and Policy Recommendations, CIFOR Occasional Paper No.37. [6] Hairiah K, Dewi S, Agus F, Velarde S, Ekadinata A, Rahayu S and van Noordwijk M (2011), Measuring Carbon Stocks Across Land Use Systems: A Manual, Bogor, Indonesia. World Agroforestry Centre (ICRAF), SEA Regional Office, 154 pages. [7] James Michael Roshetko (2013), Smallholder tree farming systems for livelihood enhancement and carbon storage, IGN PhD Thesis August 2013. Department of Geosciences and Natural Resource Management, University of Copenhagen, Frederiksberg. [8] Lalaina Cynthia Ratsimbazafy, Kazuhiro Harada, Mitsuru Yamamura (2011), Forest conservation and livelihood conflict in REDD: A case study from the corridor Ankeniheny Zahamena REDD project, Madagascar, International Journal of Biodiversity and Conservation, Vol. 3(12), pp.618-630. [9] Võ Đại Hải (2012), Nghiên cứu khả năng hấp thụ carbon của ba loài keo ở Việt Nam, Viện khoa học Lâm nghiệp Việt Nam [10] Vũ Tấn Phương (chủ nhiệm) (2007), Báo cáo tổng kết đề tài, Nghiên cứu Lượng giá kinh tế Môi trường và dịch vụ môi trường của một số loại rừng chủ yếu ở Việt Nam. Bộ Nông nghiệp và phát triển nông thôn - Viện Khoa học lâm nghiệp, Hà Nội. [11] Ngô Thế Ân, Nguyễn Thị Bích Hà (2014), “Mối liên hệ giữa sinh kế của người dân và nguồn carbon dự trữ trong thảm rừng”, Tạp chí Khoa học và Phát triển, Tập 13, số 2: 226-234. [12] Nguyễn Hải Vân, Nguyễn Việt Dũng (2015), “Sinh kế cây sắn và giấc mơ carbon REDD+ - nghiên cứu trường hợp tại xã Hiếu, huyện Kon Plong, tỉnh Kon Tum”, Toạ đàm Phát triển sắn và bảo vệ rừng ở Việt Nam-thực trạng và ý nghĩa về chính sách, ngày 17/7/2015.